2013
DOI: 10.1111/ecpo.12003
|View full text |Cite
|
Sign up to set email alerts
|

Lotteries vs. All‐Pay Auctions in Fair and Biased Contests

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…10 The total valuation that results is distinct from the mixed-strategy equilibrium probability value for bidders, which can be shown to increase in the valuation of the rent by the bidder, and decline in the number of contestants. 11 Anderson, Goeree, and Holt (1998) consider extensions to the case where bidders are subject to decision errors; Epstein, Mealem, and Nitzan (2013) consider the case of structural discrimination in awarding the prize. 12 The solutions presented below are Rubinstein (1982) and Shaked and Sutton (1984) consistent.…”
Section: Note Smentioning
confidence: 99%
See 1 more Smart Citation
“…10 The total valuation that results is distinct from the mixed-strategy equilibrium probability value for bidders, which can be shown to increase in the valuation of the rent by the bidder, and decline in the number of contestants. 11 Anderson, Goeree, and Holt (1998) consider extensions to the case where bidders are subject to decision errors; Epstein, Mealem, and Nitzan (2013) consider the case of structural discrimination in awarding the prize. 12 The solutions presented below are Rubinstein (1982) and Shaked and Sutton (1984) consistent.…”
Section: Note Smentioning
confidence: 99%
“… Anderson, Goeree, and Holt () consider extensions to the case where bidders are subject to decision errors; Epstein, Mealem, and Nitzan () consider the case of structural discrimination in awarding the prize.…”
mentioning
confidence: 99%
“…This implies that the point E, which represents the interior equilibrium taxation scheme, must be to the right of A. That is, the reduced stake of contestant 1 is S See Epstein et al (2011b). efforts by fully taking advantage of the potential "income effect" associated with a scheme that increases the sum of the final stakes from ( )…”
Section: Propositionmentioning
confidence: 99%
“…1 On the other hand, Fang (2002) and Epstein et al (2013) have shown that a contest can achieve a higher revenue than an all-pay auction in asymmetric settings; Franke et al (2014) further argue that the presence of more than two players increases the chances of contests to achieve a higher revenue. In this paper, we show that a Tullock contest can generate a higher expected revenue even in an ex-ante symmetric setting with two players.…”
Section: Introductionmentioning
confidence: 99%